The sequence of regional structural disconnectivity due to multiple sclerosis lesions - Tozlu, Ceren; Olafson, Emily; Jamison, Keith W; Demmon, Emily; Kaunzner, Ulrike; Marcille, Melanie; Zinger, Nicole; Michaelson, Nara; Safi, Neha; Nguyen, Thanh; Gauthier, Susan; Kuceyeski, Amy (Brain communications, 2023)
Abstract Prediction of disease progression is challenging in multiple sclerosis as the sequence of lesion development and retention of inflammation within a subset of chronic lesions is heterogeneous among patients. We investigated the sequence of lesion-related regional structural disconnectivity across the spectrum of disability and cognitive impairment in multiple sclerosis. In a full cohort of 482 multiple sclerosis patients (age: 41.83 ± 11.63 years, 71.57% females), the Expanded Disability Status Scale was used to classify patients into (i) no or mild (Expanded Disability Status Scale <3) versus (ii) moderate or severe disability groups (Expanded Disability Status Scale ≥3). In 363 out of 482 patients, quantitative susceptibility mapping was used to identify paramagnetic rim lesions, which are maintained by a rim of iron-laden innate immune cells. In 171 out of 482 patients, Brief International Cognitive Assessment was used to identify subjects as being cognitively preserved or impaired. Network Modification Tool was used to estimate the regional structural disconnectivity due to multiple sclerosis lesions. Discriminative event-based modelling was applied to investigate the sequence of regional structural disconnectivity due to (i) all representative T2 fluid-attenuated inversion recovery lesions, (ii) paramagnetic rim lesions versus non-paramagnetic rim lesions separately across disability groups (‘no to mild disability’ to ‘moderate to severe disability’), (iii) all representative T2 fluid-attenuated inversion recovery lesions and (iv) paramagnetic rim lesions versus non-paramagnetic rim lesions separately across cognitive status (‘cognitively preserved’ to ‘cognitively impaired’). In the full cohort, structural disconnection in the ventral attention and subcortical networks, particularly in the supramarginal and putamen regions, was an early biomarker of moderate or severe disability. The earliest biomarkers of disability progression were structural disconnections due to paramagnetic rim lesions in the motor-related regions. Subcortical structural disconnection, particularly in the ventral diencephalon and thalamus regions, was an early biomarker of cognitive impairment. Our data-driven model revealed that the structural disconnection in the subcortical regions, particularly in the thalamus, is an early biomarker for both disability and cognitive impairment in multiple sclerosis. Paramagnetic rim lesions–related structural disconnection in the motor cortex may identify the patients at risk for moderate or severe disability in multiple sclerosis. Such information might be used to identify people with multiple sclerosis who have an increased risk of disability progression or cognitive decline in order to provide personalized treatment plans. Tozlu et al. report that subcortical structural disconnectivity due to lesions identified with T2 fluid-attenuated inversion recovery occurs earlier across the spectrum of disability and cognitive impairment in people with multiple sclerosis. Paramagnetic rim lesion (PRL)–based structural disconnectivity in motor-related regions occurs earlier compared to non–PRL-based structural disconnectivity in the disability event sequence. Graphical Abstract Graphical Abstract